2021
DOI: 10.1371/journal.pone.0258763
|View full text |Cite
|
Sign up to set email alerts
|

Association between relative handgrip strength and hypertension in Chinese adults: An analysis of four successive national surveys with 712,442 individuals (2000-2014)

Abstract: Objectives This study aimed to identify the 15-year trends of handgrip strength-to-weight (relative HS) and assess the association between relative HS and hypertension among Chinese adults aged 20–69. Methods Using a complex, stratified, multistage probability cluster sampling, we analyzed data collected from 712,442 adults aged 20–69 years in four successive national surveys (2000–2014). We used a handheld dynamometer to measure strength and divided by body weight to calculate the relative HS. Blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…In our study, there was an inverse association between the sex-specific tertiles of rHGS and risk of hypertension even after adjusting for VAI and PA-time, as shown in Table 2 . This result supports previous findings of an inverse association between muscular strength and risk of hypertension ( Feng et al, 2021 ). However, considering these contradictory results, it can be inferred that the associations between muscular strength and risk of hypertension have not been fully investigated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, there was an inverse association between the sex-specific tertiles of rHGS and risk of hypertension even after adjusting for VAI and PA-time, as shown in Table 2 . This result supports previous findings of an inverse association between muscular strength and risk of hypertension ( Feng et al, 2021 ). However, considering these contradictory results, it can be inferred that the associations between muscular strength and risk of hypertension have not been fully investigated.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike in aerobic exercise training, which plays a beneficial role on vascular health including BP ( Fagard, 2006 ; Pagonas et al, 2017 ), the associations between resistance training or muscular strength and the factors related to hypertension are controversial. In several studies, higher muscular strength was associated with a lower risk of hypertension ( Maslow et al, 2010 ; Feng et al, 2021 ). However, this association between muscular strength and risk of hypertension was no longer significant after adjusting for cardiorespiratory fitness ( Maslow et al, 2010 ), and no significant correlation was found between muscular strength and risk of hypertension in a recent meta-analysis ( Bai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is worth mentioning that our negative correlation between muscle quality and hypertension prevalence was further confirmed by subgroup analysis with the uniformity of associations across wide‐ranging groups. Simultaneously, this negative association was supported by previous findings indicating that increased relative HGS (i.e., HGS standardized to BMI or body weight) is related to lower hypertension prevalence, which may be attributed to the fact that the nature of muscle quality is still a kind of relative strength 28–31 . Herein, we can conclude that relative HGS, including muscle quality, presents a more robust and plausible negative association with hypertension risk.…”
Section: Discussionsupporting
confidence: 83%
“…But contrast result showed in case of female with underweight had highest grip strength. 13 Another study by Oseloka I.A. et.al showed positive correlation of grip strength with BMI in secondary school students.…”
Section: Discussionmentioning
confidence: 95%